Toxicity of synthetic piperonyl compounds to leaf-cutting ants and their symbiotic fungus - Victor, Sandra R. [UNESP]; Vieira, Paulo C.; Fátima G F Da Silva, M.; Crisóstomo, Fernando R.; Bueno, Fabiana C. [UNESP]; Pagnocca, Fernando C. [UNESP]; Fernandes, João B.; Correa, Arlene G.; Bueno, Odair C. [UNESP]; José A Hebling, M. [UNESP]; Jr, Maurício Bacci [UNESP] (Wiley, 2001)
The development of Leucoagaricus gongylophorus, the fungus cultured by the leaf-cutting ant Atta sexdens was inhibited in vitro by synthetic compounds containing the piperonyl group. In addition, worker ants that were fed daily on an artificial diet to which these compounds were added had a higher mortality rate than the controls. The inhibition of the fungal growth increased with the size of the carbon side chain ranging from C1 through C8 and decreasing thereafter. 1-(3,4-Methylenedioxybenzyloxy)octane (compound 5) was the most active compound and inhibited the fungal development by 80% at a concentration of 15 μg m1-1. With worker ants the toxic effects started with compound 5 and increased with the number of carbons in the side chain. Thus, for the same concentration (100 μg m1-1) the mortality rates observed after 8 days of diet ingestion were 82%, 66% and 42%, for 1-(3,4-methylenedioxybenzyloxy)decane, 1-(3,4-methylenedioxybenzyloxy)dodecane and compound 5, respectively, whereas with commercial piperonyl butoxide the mortality was 68%. The latter compound, which is known as a synergist insecticide, was as inhibitory to the symbiotic fungus as the synthetic compound 5. The possibility of controlling these insects in the future using compounds that can target simultaneously both organisms is discussed. © 2001 Society of Chemical Industry.
Keywords: Antifungal activity; Atta sexdens; Leaf-cutting ant; Leucoagaricus gongylophorus; Piperonyl compounds; 1 (3,4 methylenedioxybenzyloxy)octane; antifungal agent; benzyl alcohol derivative; bromide; decane; dodecane; iodide; octane; pesticide; pipamperone; piperonyl alcohol; piperonyl butoxide; unclassified drug; ant; fungus; insecticide; symbiont; toxicity; animal; antifungal activity; atta sexdens; bioassay; chemistry; drug effect; fungus growth; metabolism; mortality; nonhuman; plant leaf; symbiosis; Animals; Antifungal Agents; Ants; Benzyl Alcohols; Biological Assay; Bromides; Fungi; Iodides; Pesticide Synergists; Piperonyl Butoxide; Plant Leaves; Symbiosis; Formicidae; Hexapoda